Comparison of Ephedrine Versus Lidocaine in Reducing the Frequency of Pain on Propofol Injection during Elective Surgeries - Sumbal Rana (Journal of Rawalpindi Medical College, 2017)
Background: To compare the ephedrine with lidocaine for reducing frequency of pain on propofol injection during elective surgeries. Methods: In this randomized controlled trial 80 patients were observed by taking 40 patients in each group, i.e. group A: ephedrine group and group B:lidocaine group. Patients with ASA–I (normal healthy patient), II (mild systemic disease with no functional limitation) aging between 20 and 40 years and opting for elective surgical procedures were included. The pain intensity was classified in four levels from no pain to severe pain. The frequencies of pain intensity were recorded during the injection period before the loss of consciousness according to the verbal rating scale (VRS) explained to patients at the preoperative visit. Chi square test was used to compare the frequency of pain in two groups, where p-value <0.05 was considered statistically significant. Effect modifiers i.e. the age, gender and ASA were controlled by stratification. The post stratification Chi-square test was applied keeping the p-value <0.05 as significant. Results: In Group A, 35% complained of severe pain, 42.5% had moderate pain, 22.5% had mild pain and no patients reported absence of pain as per our operational definition. In Group B 47.5% reported no pain during propofol injection, 40% complained of mild pain, 12.5% had moderate and no patients reported severe pain. The p-value is 0.00. Conclusion: Pretreatment with lidocaine resulted in significantly better pain control during propofol infusion than pretreatment with ephedrine